Объёмная вязкость в жидкостях и в жидких дисперсных системах; Известия вузов. Физика; Т. 65, № 5 - Дамдинов Б. Б. Баир Батуевич; Митыпов Ч. М. Чингиз Мункоевич; Ершов А. А. Александр Андреевич; Ан В. В. Владимир Вилорьевич (2022, 2022)
Заглавие с экрана